NEED ASSESMENT SEBAGAI MANIFESTASi UNJUK KERJA KONSELOR - YAUMIL AFIAT; WAHIDAH FITRIANI1; TITANIA FITRI AISYAH (Universitas Islam Negeri Mataram, 2021)
This study aims to describe urgency need assessment in improving the performance counselors and describe the skills of counselors in conducting need assessments. The method in this research is descriptive quantitative. The population 330 people. The sample in this study amounted to 100 people who were taken by simple random sampling technique. The results of this study indicate that 59% of BK teachers are skilled in the implementation and praxis of need assessment. However, there are 39% of BK teachers who are not yet skilled in the implementation and praxis of need assessment. In fact, there are still 2% of teachers who are not skilled in this matter. In addition, the program prepared by the counselor only reflects routine activities as a requirement to fulfill administrative completeness, not a reflection of the professional views, attitudes, and beliefs of the counselor regarding the purpose of service implementation, especially to students as service targets. The solution offered to deal with the problem of lack of counselor skills in the implementation and praxis of this need assessment is through socialization in the form of in-service training related to the importance of need assessment as the basis for making BK programs.